2004
DOI: 10.1074/jbc.m409605200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disruption of the Plasmodium falciparum Digestive Vacuole Plasmepsins Demonstrates Their Functional Redundancy

Abstract: The digestive vacuole plasmepsins PfPM1, PfPM2, PfPM4, and PfHAP (a histoaspartic proteinase) are 4 aspartic proteinases among 10 encoded in the Plasmodium falciparum malarial genome. These have been hypothesized to initiate and contribute significantly to hemoglobin degradation, a catabolic function essential to the survival of this intraerythrocytic parasite. Because of their perceived significance, these plasmepsins have been proposed as potential targets for antimalarial drug development. To test their ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 60 publications
4
105
0
3
Order By: Relevance
“…Previous studies have shown that individual knockouts of each of the four food vacuole plasmepsins and falcipain-2 have nearly normal growth phenotypes in RPMI medium 1640 (5,16,17). A plasmepsin IV͞I double knockout has a doubling time Ï·10% longer than the parental strain; this phenotype is accentuated slightly in 5AA (5).…”
Section: Growth Of Hemoglobin Degradation Enzyme Gene Knockout Lines Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that individual knockouts of each of the four food vacuole plasmepsins and falcipain-2 have nearly normal growth phenotypes in RPMI medium 1640 (5,16,17). A plasmepsin IV͞I double knockout has a doubling time Ï·10% longer than the parental strain; this phenotype is accentuated slightly in 5AA (5).…”
Section: Growth Of Hemoglobin Degradation Enzyme Gene Knockout Lines Inmentioning
confidence: 99%
“…Inhibitors of aspartic and cysteine proteases kill parasites in culture and animal models, although their specificity is not strict (13)(14)(15). Knockouts of plasmepsins individually or in combination (plasmepsin IV͞I double knockout) give parasites with only slightly impaired growth (5,16), and a falcipain-2 knockout shows normal growth (17). The effect of aspartic protease inhibitors is potentiated when combined with cysteine protease inhibitors or used in falcipain-2 knockout parasites (15,17).…”
Section: Degradation Of Host Hemoglobin By the Human Malaria Parasitementioning
confidence: 99%
“…13,18,19 However, knockout experiments have shown that the DV plasmepsins and falcipains 2 and 2â€Č are individually not essential to parasite survival, and because of this redundancy between the function of these enzyme classes it has proved difficult to develop drugs that effectively block the digestive process within the DV. [21][22][23][24] Peptides produced in the DV may be further processed to dipeptides by a dipeptidyl aminopeptidase I, an orthologue of mammalian cathepsin C. 25,26 Small peptides and dipeptides may also be reduced to free aminoacids within the DV and/or transported to the parasite cytosol for processing by aminopeptidases. 20,[27][28][29][30][31][32][33] Aminopeptidases are essential in releasing aminoacids from haemoglobin-derived peptides and are thus central to the growth and development of malaria parasites in the erythrocyte.…”
Section: -16mentioning
confidence: 99%
“…The diaryl ureas presented herein, however, do not appear to significantly target the plasmepsins as they equally inhibit the growth of both wild type and knockouts of PfPM1 through 4 (See Supplementary Data Table S1), attained via a genetic disruption methodology in the Dd2 background. 20 GlaxoSmithKline disclosed the whole-cell efficacy of screening hit TCMDC-139010 (Supplementary Data Figure S1; XC 50 = 930 nM vs. 3D7 strain), but without information concerning the biochemical target. 4 We also reported in 2005 the preparation of triclosan-based 4'-ureas (Supplementary Data Figure S1) that were less potent against cultured parasite (EC 50 values of ~100 ÎŒM) than 12 -25, but exhibited IC 50 values of ~100 nM against purified PfFabI assayed in vitro.…”
mentioning
confidence: 99%